Biological characteristics of the hydrological landscapes in the Bay of Biscay in spring 2009. (19th January 2015) - Lezama‐Ochoa, Ainhoa; Grados, Daniel; Lebourges‐Dhaussy, Anne; Irigoien, Xabier; Chaigneau, Alexis; Bertrand, Arnaud
Abstract In the present study we investigated the biogeography of macrozooplankton and fish biomass in the Bay of Biscay. In this region, we defined six different landscapes based on the hydrogeographical characteristics observed in spring 2009. We then related landscape's characteristics and environmental parameters such as light attenuation depth and chlorophyll‐a with macrozooplankton and fish acoustic biomass. Hydrodynamic structures together with coastal influences (river discharges, predation pressure and depth preference) and vertical thermohaline structure/mixing (feeding modes and ability to stay in preferred layers) appeared as the main factors determining the biological distribution. Besides, variance partitioning was used to assess the respective roles played by the hydrological environment, the geographical space and the biological environment alone, and their interactions. Results revealed that: (i) macrozooplankton and fish have a preference for different hydrogeographical landscapes; (ii) the association between hydrological conditions and geographical features, i.e. the spatial structure of the hydrological environment, plays a key role in the distribution of macrozooplankton; and (iii) prey–predator relationships have to be taken into account to provide a comprehensive characterization of habitat suitability.